PENGARUH PERLAKUAN PENYIMPANAN TERHADAP VIABILITAS RIMPANG JAHE PUTIH KECIL - Melati, Melati; Rusmin, Devi (JURNAL AGRONIDA, 2018)
One problem for developing small white ginger (Zingiber officinale var. Â amarum) is the availability of high quality rhizome seeds in right Â quantity and time. Seed rhizome will sprout quickly, and its quality will decreased in immature seed rhizome and in not good storage conditions. The main objective of the experiment was to study the best storage room conditions for storage rhizome seeds of small white ginger. Â The experiment was conducted in seed laboratory and storage room of Research Institute for Medicinal and Aromatic Crops Bogor. The experimentÂ  was conducted by randomized complete design with nine different storage, 3 replication and 25 samples each treatment.Â  The treatments are 1) rhizome seeds Â storage in room temperature (control),(2) rhizome seeds storage in AC room (16â240C),(3) rhizome seedÂ  soaked in paclobutrazol 1000 ppm for 4 hours then seeds storage Â in room temperature ( 4) put rhizome seeds in rack and cover by straw, storage in Â Â room temperature (5) rhizome seed storage on straws in the greenhouse ( 6) rhizome seed storage in the greenhouse without straw ( 7) rhizome seed soaked in water during 1 hour everyÂ  month then dried naturally in 300C and storageÂ  in AC room (8) rhizome seed soaked in paclobutrazol 1000 ppm for 4 hour then storageÂ  in AC room ( 9) put rhizome Â in wood box and cover by rice straw and husk. Variables observed include moisture contents of ginger seed, lost weight of seed and germination percentage of rhizome seeds at the end of storage period. The result of experiment indicated thatÂ  the moisture content and weight rhizome seeds decrease after 2 months. After four months storage period, moisture content was still highÂ  above 80 %, except rhizome seeds in under ground.Â  The rhizome seeds that store in AC room showed the best performance and thus, this treatment can be recommended for storage of small white ginger rhizome seeds for 4 months. The low moisture content Â (< 80%) of rhizome small white ginger seeds will decreased Â its viability.Â  Â Keywords: Zingiber officinale, seed, storage, viability